Compactness in Wiener amalgams on locally compact groups - S. S. Pandey (International Journal of Mathematics and Mathematical Sciences)
We study the compactness of bounded subsets in a Wiener amalgam whose local and global components are solid Banach function (BF) spaces on a locally compact group. Our main theorem provides a generalization of the corresponding results of Feichtinger. This paper paves the way for the study of compact multiplier operators on general Wiener amalgams on the lines of Feichtinger.